Does Altitude Effect on Species Composition and Diversity on Himalayan Rangeland? - Limbu, Dilkumar; Koirala, Madan; Shang, Zhanhuan (Himalayan Journal of Science and Technology, 2017)
Himalayan rangelands have diverse floristic composition and important ecological services. The floristic diversity and composition play an important role in grassland ecosystem regulation. It is different in altitudinal gradient due to grazing intensity, climatic condition and topography. To reveal the vegetation composition values, this work was conducted on August and September 2011 in Tinjure-Milke mountain ridge, Guphapokhari, Nepal. In the present study we have described the impact of altitude on the species richness, species diversity and dispersion behavior of different plants (grasses) in Himalayan rangeland. The values of community indices were observed to be: RD (0.09 to 49.57), RF (3.57 to 14.71), RA (0.23 to 47.59), IVI (3.89 to 111.87), Shannan-Wiener diversity index (1.09 to 2.23) and species diversity evenness (0.12 to 0.19) at the study area, MilkeJaljale, eastern Nepal. Similarly, Species richness (R) value of 8.87 to 11.86 and Simpson dominant index value of 0.12 to 0.42 were observed. All diversity indices were reversed to altitudinal gradient higher the altitudes lower the values. Species richness of all plants showed a unimodal relationship with altitude. Similarly, negative correlation of density and species richness with altitude and slope was recorded.